Squamous metaplasia of the tracheal epithelium in children. Issue 2 (April 1976) - Mithal, A; Emery, J L
Abstract : Thirty-seven (1-6%) tracheas from 2170 children showed squamous metaplasia. (Cases with tracheo-oesophageal fistula and congenital heart disease were excluded). The metaplasia extended into the bronchi in 15 cases. Features of pulmonary retention were present in seven cases. Respiratory infection, probably viral, seemed to be the most significant causative factor in 20 children, including those with cystic fibrosis. Tracheal instrumentation was a possible factor in 11 cases but oxygen therapy alone did not seem important. The metaplasia was almost certainly congenital in one child and probably in two others but no stillborn infants showed metaplasia. In many children the metaplasia seemed to be due to a combination of factors.